2013
DOI: 10.1007/s11626-013-9581-9
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity alters the metastatic potential of a human lung adenocarcinoma cell line

Abstract: Simulated microgravity (SM) has been implicated in affecting diverse cellular pathways. Although there is emerging evidence that SM can alter cellular functions, its effect in cancer metastasis has not been addressed. Here, we demonstrate that SM inhibits migration, gelatinolytic activity, and cell proliferation of an A549 human lung adenocarcinoma cell line in vitro. Expression of antigen MKI67 and matrix metalloproteinase-2 (MMP2) was reduced in A549 cells stimulated by clinorotation when compared with the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 27 publications
6
41
0
Order By: Relevance
“…Jing Li et al found that microgravity had closely associated with changing focal adhesion and cytoskeleton, and decreasing migration potential in human breast carcinoma [7]. De Chang et al also found that microgravity inhibited migration and invasion of human lung adenocarcinoma cell line [8]. Thus, MMG might have distinct effects on inhibiting the invasion and migration potentials in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jing Li et al found that microgravity had closely associated with changing focal adhesion and cytoskeleton, and decreasing migration potential in human breast carcinoma [7]. De Chang et al also found that microgravity inhibited migration and invasion of human lung adenocarcinoma cell line [8]. Thus, MMG might have distinct effects on inhibiting the invasion and migration potentials in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Jing Li et al found that microgravity insult would change the cytoskeleton and focal adhesions, and decrease migration in human breast carcinoma [7]. De Chang et al found that microgravity treatment inhibited cell proliferation, migration, and invasion of human lung adenocarcinoma cell line [8]. Meanwhile, after microgravity insult, differentiation alteration and apoptosis increase have been found in human follicular thyroid carcinoma cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to originate clones in PBLs incubated for 48h and 72 h decreased in both gravity conditions probably because the longer G 0 -phase condition experienced by PBLs affected their responsiveness to enter into cell cycle. The antiproliferative effect of microgravity has been recently reported also in human thyroid cancer cells [96] and in human lung adenocarcinoma cells [97]. Our results of apoptosis induction demonstrated that both the formation of apoptotic bodies activation and caspase-3 activation increased significantly in PBLs incubated in MMG than in 1 g. The activation of apoptotic process seems related to the overexpression of PDCD4 and RELA rather than to the underexpression of BNIP3L and APAF1, indicating the existence of complex regulatory networks between miRNAs and mRNAs that occur at different levels of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Chang et al investigated altered gravity effects on human lung adenocarcinoma, demonstrating the ability of simulated microgravity to decrease the metastatic potential of this tumor cell line. 11 Other researchers used microgravity stimulation as an approach for the development of a large amount of β-cell spheroids, which once transplanted in mice are able to improve the symptoms of diabetes. 12 Among different tissues, bone is particularly affected by altered gravity conditions: evidence regarding bone regeneration suggests that hypergravity exposure -conversely to microgravity, which negatively affects osteogenesis -may enhance the osteogenic potential of osteoblast precursors.…”
mentioning
confidence: 99%